Flashcard for Enriching and Developing the Child Vocabulary with Speech Delay to Improve Lingual Skill - C Dahniarti; M Siti; A Fajar (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This study aims to enrich and developing vocabulary the child with speech delay by using flashcard. The subject of the research is the child who was late in speaking due to sensory disorders, Kindergarten 1, the age of 4 years old. The research method was single subject research quantitative research (single subject research). Techniques of analysis the data collection through observation of  baseline A and B, also documentation. The Results showed that baseline phase (A) phase to the intervention (B) are increasing, which means that the condition has increased after the intervention. Where in the baseline-2 (A2) phase to intervention (B) it is increased which means that the intervention can significantly improve the ability of the subject.